Research Developments on Flexitime: A Bibliometric Analysis - Kuswandi, Luthfianisa; Nugraha, Yayang Yulia (STIE Ekuitas, 2025)
Introduction/Main Objectives: The phenomenon of the increasing need for work flexibility in various countries has prompted many organizations to adopt flexitime work systems. This study aims to examine publication related to flexitime and its associations with work-life balance, jo satisfaction, and employee well-being, with a specific emphasis on female employees. Background Problems: The publication trend on flexitime has fluctuated from 1976 to 2024, with minimal publications before 1990. Since the early 2000s, the number of publications has steadily increased, driven by heightened attention to work-life balance and the evolving dynamics of the workforce. Novelty: Unlike previous studies, this research specifically examines the evolution of flexitime publications and quantitatively maps its research connections using bibliometric analysis. Research Methods: A bibliometric analysis was conducted using data from the Scopus database, analyzing 92 publications from 1976 to 2024. VOSviewer was used to visualize research trends in publication frequency, country contributions, co-authorship networks, and keyword co-occurrences. Finding/Results: The study reveals a significant rise in flexitime research since the early 2000s, correlating with increased discussions on work-life balance and employee well-being. The bibliometric analysis highlights key research clusters and gaps in existing literature. Conclusion: Flexitime research has evolved significantly, reflecting its growing importance in workforce management. However, significant gaps remain in understanding the challenges associated with implementation, the role of government policies, and the integration of technology and digital tools. Future reseach should address these issues to foster a more flexible, inclusive, and productive work environment.